Russian public sector reform: The impact on university accounting - Timoshenko, Konstantin (Journal of Business Economics and Management, 2008)
The last few decades have witnessed substantial efforts to reinvent the state worldwide. The Russian state is no exception to this global trend. At the outset of a new millennium, the need for renewal of the post‐Soviet model of the state has been acknowledged, and an up‐to‐date reform package has been promoted by the central government. This has encompassed the reconstruction of public sector accounting. Given the paucity of consistent research efforts on the topic, this article seeks to describe and analyze, and by so doing, contribute to knowledge about Russian public sector accounting in times of change. To tackle the general purpose, two levels are incorporated in this study to link reform initiatives for the government as a whole with those endeavours to implement them in one state‐sponsored university of Russian tertiary education. The major questions to be addressed are of whether, why, and how changes at the central government level have penetrated down to the university and extended to its accounting system. The evidence gathered in this paper reveals that a new Russian public sector ideology has markedly been affected by overseas developments in the shape of large international organizations. However, no compelling evidence has been documented in this research as unveiling that changes at the macro‐level have penetrated down to the university to any significant extent. This study concludes that launching a new version of accounting by the Russian state can be regarded as more of a symbol of legitimacy for the university rather than of an actual financial management tool. First published online: 14 Oct 2010